Clinical Approach to Immunotherapy-induced Type 1 Diabetes Mellitus: A Case of Pembrolizumab Associated Insulin-dependent Diabetes in a Patient with NSCLC - Ntertsos, Nikolaos; Christantoniou, George; Kyrka, Krystallia; Pezirkianidou, Persefoni; Bikos, Vasileios; Konstantina, Papadaki; Tsiouda, Theodora (Journal of Pulmonology and Respiratory Research, 2023)
As the introduction of immune checkpoint inhibitors in the treatment of various cancers is now proven to be already acquired knowledge, so does a new challenge arise for clinicians; the understanding, diagnosis, and management of the rarest adverse effects of immunotherapy. We present a case of type-1 diabetes Mellitus (T1DM) in a patient with non-small cell lung carcinoma (NSCLC) treated with pembrolizumab. Following ten cycles of treatment, our patient was diagnosed with T1DM after being admitted for diabetic ketoacidosis and stayed hospitalized in the ICU. Later, they continued treatment with insulin, having shown disease response to pembrolizumab, and resumed immunotherapy while on insulin. Immunotherapy-induced T1DM can sometimes occur with PD1/PD-L1 blockage therapies. It has a rapid onset, is characterized by insulin deficiency due to the autoimmune destruction of beta-cells, and usually presents itself with diabetic ketoacidosis. Unlike most of the other adverse effects of immunotherapy, glucocorticoids don’t seem to be of therapeutic value, and insulin substitution is required. Regular glucose monitoring can be key to early diagnosis and prevention of hospitalization.